NILAI-NILAI SOSIAL PADA UPACARA KEMATIAN SARI MATUA DI KALANGAN BATAK TOBA DI KOTA PEKANBARU - Fransiska Fitri Yanti.P; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Sari Matua's death ceremony is a traditional ceremony which is carried out as a form of final respect for a husband or wife who has been blessed with the grandchildren of his children even though there are still unmarried children in the Toba Batak culture. This ceremony has an important meaning and role from every element of society, especially the traditional leaders and the people who are as valuable as they are. This study aims to examine the ceremonies of the death of Sari Matua in Toba Batak culture with the focus of the problem is to find out the meaning and social values contained in the Sari Matua death ceremony. The research method used is descriptive qualitative by mentioning the theory used is symbolic interactionism supported by the results of observations and interviews of informants, namely traditional leaders and the Toba Batak community in the Pekanbaru area. The results showed that the process of carrying out the Sari Matua death ceremony was carried out by the king, at home, in the yard, in a place of worship, in a funeral using local musical instruments. Slaughter of certain animals that have meaning in the customary genealogy that is being carried out (buffalos and pigs) by sharing jambas in accordance with the role and position of traditional leaders and communities in the Toba Batak tradition. The meaning of Sari Matua's death ceremony is to respect the parents of the deceased, to establish unity and unity among the family as well as the scope of the transfer of natolu pahopaton sihal-sihal. The problem faced by the community in the implementation of this ceremony is that sufficient material is needed to prepare for the event so that some people do not carry out this ceremony properly. The need to work hand in hand so that cultural and family values in the Toba Batak tradition are maintained.  Key Word: Sari Matua's Death Ceremony; Toba Batak Death Ceremony